The MocR/GabR Ectoine and Hydroxyectoine Catabolism Regulator EnuR: Inducer and DNA Binding - Hermann, Lucas; Dempwolff, Felix; Steinchen, Wieland; Freibert, Sven-Andreas; Smits, Sander H. J.; Seubert, Andreas; Bremer, Erhard (Frontiers in Microbiology, 2021)
The compatible solutes ectoine and 5-hydroxyectoine are widely synthesized by bacteria as osmostress protectants. These nitrogen-rich tetrahydropyrimidines can also be exploited as nutrients by microorganisms. Many ectoine/5-hydroxyectoine catabolic gene clusters are associated with a regulatory gene (enuR: ectoine nutrient utilization regulator) encoding a repressor protein belonging to the MocR/GabR sub-family of GntR-type transcription factors. Focusing on EnuR from the marine bacterium Ruegeria pomeroyi, we show that the dimerization of EnuR is mediated by its aminotransferase domain. This domain can fold independently from its amino-terminal DNA reading head and can incorporate pyridoxal-5’-phosphate (PLP) as cofactor. The covalent attachment of PLP to residue Lys302 of EnuR was proven by mass-spectrometry. PLP interacts with system-specific, ectoine and 5-hydroxyectoine-derived inducers: alpha-acetyldiaminobutyric acid (alpha-ADABA), and hydroxy-alpha-acetyldiaminobutyric acid (hydroxy-alpha-ADABA), respectively. These inducers are generated, in cells actively growing with ectoines as sole carbon and nitrogen sources, by the EutD hydrolase and targeted metabolic analysis allowed their detection. EnuR binds these effector molecules with affinities in the low micro-molar range. Studies addressing the evolutionary conservation of EnuR, modelling of the EnuR structure, and docking experiments with the inducers provide an initial view into the cofactor and effector binding cavity. In this cavity, the two high-affinity inducers for EnuR, alpha-ADABA and hydroxy-alpha-ADABA, are positioned such that their respective primary nitrogen group can chemically interact with PLP. Purified EnuR bound with micro-molar affinity to a 48 base pair DNA fragment containing the sigma-70 type substrate-inducible promoter for the ectoine/5-hydroxyectoine importer and catabolic gene cluster. Consistent with the function of EnuR as a repressor, the core elements of the promoter overlap with two predicted EnuR operators. Our data lend themselves to a straightforward regulatory model for the initial encounter of EnuR-possessing ectoine/5-hydroxyectoine consumers with environmental ectoines and for the situation when the external supply of these compounds has been exhausted by catabolism.